Reverse movements of red knots Calidris Canutus during northward migration in Argentina - D'amico, Veronica Laura; Gonzalez, Patricia M.; Guy Morrison, R. I.; Baker, Allan J. (Ardeola)
Migratory birds are sometimes known to make reverse movements to seek better fueling sites before undertaking long-distance migratory flights across ecological barriers. Red Knots (Calidris canutus rufa) regularly make prodigious migratory flights of ~ 8000 km from southern South America to North America; these flights depend critically on the birds being able to store adequate fuel at southern staging sites. Knots staging at San Antonio Oeste (SAO) in northern Patagonia in Argentina could potentially backtrack ~200 km southwards to complete refueling at Península Valdés (PV). We therefore analyzed resightings of birds individually marked in SAO or the flyway at these two staging sites in 2006, 2007, 2009 and 2010 to investigate whether reverse movements occurred between them. In the 4-year period, 63 detected individuals backtracked south from SAO to PV in one or more years; these movements occurred in all years of the study thus demonstrating the annual occurrence of flights of ~200 km in the opposite direction to the normal northward migration. There was no significant difference in body condition (mass), sex or day of first sighting in SAO between birds that made or did not make reverse movements to PV. However, individuals (N = 11) that backtracked to PV from SAO had significantly lower hematocrit levels at the time of capture than SAO resident birds (N = 205). Because migrating shorebirds have been shown to restore low hematocrit levels before undertaking rapid fuel storage to power long flights, we hypothesize that Red Knots backtracking to PV were likely behind schedule in migration, and thus may have traded-off the small cost of a ~200 km flight for the increased foraging time and high quality soft-shell prey available late in the season in PV. This hypothesis helps to explain the later staging phenology of Red Knots using PV, and its role as an alternative staging area in the northward migration. Las aves limícolas migratorias suelen realizar migraciones reversas con el fin de buscar mejores lugares ...